Capacity Study Of Lithium Ion Battery For Handphones - Khalid Khairulanam bin Mohd Ramli, Khalid Khairulanam (2010)
This project is to study about the capacity of various types of lithium-ion (Li-ion) batteries for handphones. The battery models developed from this project is using MATLAB/Simulink. The model has been developed in order to investigate the output characteristics of lithium-ion batteries.